(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The analysis put forward in this work is aimed at providing evidence that, in the UK, appealing to the concepts of nature and (un)naturalness in the context of end-of-life decisions is neither morally nor legally desirable. Through inquiring into the function and meaning of these ideas, it will be determined what consequences derive from their use, and why such implications raise concern. In particular, with regard to the moral analysis it will be shown that all the interpretations given to these concepts prove to be flawed, either because they lack conceptual autonomy or because they rely on unrealistic or morally irrelevant definitions of nature and (un)naturalness; or again, as in the case of natural law, because they are not coherent with their theoretical foundations, and, even worse, they come up to unpleasant approaches to medical ethics, such as vitalism. Similarly, the legal relevance of the concepts of nature and (un)naturalness proves to be particularly flimsy. They are not a decisive factor in establishing causation in the cases of withholding and withdrawing of life-sustaining treatments, which instead hinges on the existence of a duty to act; whereas, if understood in terms of compliance with the natural law principles of practical rationality they find very little application in the relevant English law.